Socialização entre alunos pagantes e bolsistas no Colégio Rainha da Paz - Souza, Marcio Lellis de (2017)
The present work took as a study object the singular condition of socialization among paying students, residing in elite neighborhoods, and scholarship students, from outskirts of the city of São Paulo, present at Colégio Rainha da Paz, located in Alto de Pinheiros, in São Paulo’s west zone. Responding to the new legal determinations on philanthropy in private elementary schools, Colégio Rainha da Paz has implemented its philanthropic policy with the enrollment of students from lower classes under the same student activities as paying students, children of elites and wealthy classes. Starting from the understanding that the socialization between paying students and scholarship holders is a decisive element for the latter to access the academic excellence the school institution offers, this work resorted to research instruments which allowed, at first, to measure the social relations between these two groups of students. Therefore, the sociometric test created by Levy Moreno and amended by George Bastin (1966) was used. In a second stage, semi-directive interviews were carried out with scholarship students in order to qualify the exclusion pointed out in Elementary School and the revealed acceptance in High School. The interviews were analyzed deploying two categories: “friendship”, taking as reference the work of Santos (1994), and “territory and territoriality”, from Haesbaert (2011) and Santos (2001). The aim of this study was to analyze whether the long and compulsory daily coexistence between students of different social classes could bring them closer together, thus overcoming the social stigmas produced in society, or if school socialization reproduced the elements that separate them, consequently maintaining the configuration Norbert Elias described as “established and outsiders”